Factors associated with tobacco use among Nepalese men aged 15–49 years: Data from Nepal demographic and Health Survey 2016 - Gupta, Rajat Das; Jahan, Mahmuda; Hasan, Mehedi; Sutradhar, Ipsita; Sajal, Ibrahim Hossain; Haider, Shams Shabab; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (Elsevier, 2022)
This article was published in Clinical Epidemiology and Global Health [ © 2020 INDIACLEN. Published by Elsevier, a division of RELX India, Pvt. Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.cegh.2020.01.014 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S2213398420300221